A case of hepato-biliary infection secondary to cryptosporidium in a patient on tacrolimus. (20th July 2018) - Gupta, Sajal; Johnson, Alison; Meyrick, Simon; Davies, Angharad P.; Chalmers, R.
Abstract : Introduction. Cryptosporidium infection is known to cause hepato-biliary involvement, mainly in association with T-cell immune deficiency. Hepato-biliary involvement in association with milder immunosuppression is less well described. We describe the first case, to our knowledge, of Cryptosporidium hominis hepato-biliary infection associated with tacrolimus in a patient with nephrotic syndrome. Case presentation. A 14 year old girl who had been on tacrolimus for nephrotic syndrome presented with diarrhea due to C. hominis . Nineteen days after her initial presentation she attended hospital with abdominal pain and deranged liver function tests. An ultrasound scan showed a thickened gall bladder. Her symptoms settled and her liver function tests returned to normal after treatment with nitazoxanide. Conclusion. Cryptosporidium should be considered in the differential diagnosis of both diarrhea and hepato-biliary symptoms and abnormal liver function tests, even in the presence of relatively mild immunosuppression. Nitazoxanide was an effective treatment in this case.